Exploring prebiotic properties and its probiotic potential of new formulations of soy milk-derived beverages - Rana, Ananya; Taneja, Neetu Kumra; Raposo, António; Alarifi, Sehad N.; Teixeira-Lemos, Edite; Lima, Maria João; Gonçalves, João Carlos; Dhewa, Tejpal (Frontiers in Microbiology, 2024)
The food and beverage industry has shown a growing interest in plant-based beverages as alternatives to traditional milk consumption. Soy milk is derived from soy beans and contains proteins, isoflavones, soy bean oligosaccharides, and saponins, among other ingredients. Because of its high nutritive value and versatility, soy milk has gained a lot of attention as a functional food. The present work aims to explore the prebiotic properties and gastrointestinal tolerance potential of new formulations of soy milk-derived drinks to be fermented with riboflavin-producing probiotic Lactiplantibacillus plantarum MTCC (Microbial Type Culture Collection and Gene Bank) 25432, Lactiplantibacillus plantarum MTCC 25433, and Lactobacillus acidophilus NCIM (National Collection of Industrial Microorganisms) 2902 strains. The soy milk co-fermented beverage showed highest PAS (1.24 ± 0.02) followed by soy milk beverages fermented with L. plantarum MTCC 25433 (0.753 ± 0.0) when compared to the commercial prebiotic raffinose (1.29 ± 0.01). The findings of this study suggested that the soy milk beverages exhibited potent prebiotic activity, having the ability to support the growth of probiotics, and the potential to raise the content of several bioactive substances. The higher prebiotics activity score showed that the higher the growth rate of probiotics microorganism, the lower the growth of pathogen. For acidic tolerance, all fermented soy milk managed to meet the minimal requirement of 10 6 viable probiotic cells per milliliter at pH 2 (8. 13, 8.26, 8.30, and 8.45 logs CFU/mL, respectively) and pH 3.5 (8.11, 8.07, 8.39, and 9.01 log CFU/mL, respectively). The survival rate of soy milk LAB isolates on bile for 3 hours ranged from 84.64 to 89.60%. The study concluded that lactobacilli could thrive in gastrointestinal tract. The sensory evaluation scores for body and texture, color, flavor, and overall acceptability showed a significant difference (p<0.05) between the fermented probiotic soy milk and control samples. Soy milk fermented with a combination of L. plantarum MTCC 25432 & MTCC 25433 demonstrated the highest acceptability with the least amount of beany flavour. The findings of the study suggest soy milk's potential in plant-based beverage market.